Enhanced red upconversion emission and its mechanism in Yb3+–Er3+ codoped α-NaLuF4 nanoparticles. (11th January 2017) - Lin, Hao; Xu, Dekang; Li, Anming; Qiu, Zhiren; Yang, Shenghong; Zhang, Yueli
Abstract : Red upconversion luminescence is greatly enhanced through manipulation of the initial solution pH. Abstract : A series of Yb 3+ –Er 3+ codoped α-NaLuF4 nanoparticles were prepared via a hydrothermal process. Enhanced red upconversion (UC) luminescence can be achieved by adjusting the initial solution pH, and the intensity of red emission (660 nm) is enhanced 23 times. By establishing rate equations, a theoretical model about the red UC mechanism is presented. It is proposed that the highly efficient red UC emission is mainly due to the UC process from the saturated 4 I13/2 (Er 3+ ) state, which is induced by the effective energy-back-transfer process (primary): 4 S3/2 (Er 3+ ) + 2 F7/2 (Yb 3+ ) → 4 I13/2 (Er 3+ ) + 2 F5/2 (Yb 3+ ) and the cross-relaxation effect among Er 3+ (minor): 4 S3/2 + 4 I15/2 → 4 I9/2 + 4 I13/2 at a high pH value of the initial solution. Moreover, the influence of solution pH on the red UC luminescence is systematically studied under different hydrothermal conditions. This paper provides an effective route to obtain nanoparticles with bright red UC luminescence, which may be suitable for biological imaging and display devices.